Assessment of Students’ Problem-Solving Proficiency in Mathematics at Grade VI - Ghazala Noureen, Itrat Irfan, Riffatun Nisa Awan (PJE, 2023)
This study was designed to develop problem solving test for class six and also assess student’s problem solving proficiency. A test is constructed by using Framework of Mathematics Assessment developed by National Assessment of Educational Progress (NEAP). This framework is modified as Mathematics Problem-Solving proficiency framework by keeping in view the objectives of National Curriculum for 6th grade. Initially developed items were tried out and items for final test were selected by keeping in view the criteria of Item Response Theory (IRT). IRT provide guidance to develop the items and to construct the proficiency scales. IRT gives us a way to understand and interpret scores and also link student’s achievement to their latent abilities. Final test was administered to 1500 students of four districts. Students’ mean score in Algebra is greater than any other content area while performance in Ratio and Proportion is low. Therefore, students’ problem-solving proficiency in the area of factors and multiples, geometry, integers, information handling, linear equations, and whole numbers is average.